Цитогенетические механизмы адаптации и эволюции видов - Стегний, В.Н. (Фактори експериментальної еволюції організмів, 2014)
The analysis of own and literature data meaning fully chromosomal speciation and polymorphism in genetic adaptation species and in particular on the role inversion polymorphism show the connection between the frequency of chromosomal inversions dynamics due to thermal mode of existence populations. Long-term trend reversal frequency in the malaria mosquito population Anopheles messeae explains the effects of global warming.